The "chicken-leg anastomosis": Low-cost tissue-realistic simulation model for esophageal atresia training in pediatric surgery - Francesca Palmisani; Patrick Sezen; Elisabeth Haag; Martin L. Metzelder; Wilfried Krois (Frontiers Media S.A., 2022)
IntroductionShifting the training from the operating room (OR) to simulation models has been proven effective in enhancing patient safety and reducing the learning time to achieve competency and increase the operative efficiency. Currently the field of pediatric surgery only offers few low-cost trainers for specialized training and these feature predominantly artificial and often unrealistic tissue. The aim of this study was to develop an easy access low-cost tissue-realistic simulation model for open training of esophageal atresia and to evaluate the acceptance in trainees and junior pediatric surgeons.Materials and methodsThe model is fashioned using reconfigured chicken skin from a chicken leg. To create a model of esophageal atresia, the chicken skin is dissected off the muscle and reconfigured around a foley catheter balloon to recreate the proximal pouch and a feeding tube to recreate the distal pouch. Surrounding structures such as the tracheo-esophageal fistula and the azygos vein can be easily added, obtaining a realistic esophageal atresia (Type C) prototype. Evaluation of model construction, usage and impact on user were performed by both a self-assessment questionnaire with pre- and post-training questions as well as observer-based variables and a revised Objective Structured Assessment of Technical Skills (OSATS) score.ResultsA total of 10 participants were constructing and using the model at two different timepoints. OSATS score for overall performance was significantly higher (p = 0.005, z = −2.78) during the second observational period [median (MD): 4,95% confidence interval CI: 3.4, 5.1] compared to the first (MD: 3, 95% CI 2.4, 4.1). Self-reported boost in confidence after model usage for performing future esophageal atresia (EA) repair and bowel anastomosis (BA) in general was significantly higher (EA: U = 1, z = −2.3, p = 0.021, BA: U = 1, z = −2.41, p = 0.016) in participants with more years in training/attending status (EA MD:5, BA MD: 5.5) compared to less experienced participants (EA MD: 1.5, BA: 1).ConclusionOur easy access low-cost simulation model represents a feasible and tissue realistic training option to increase surgical performance of pediatric surgical trainees outside the OR.